Zdrava radna organizacija: što je i kako je ostvariti u hrvatskom kontekstu? (Morepress Books, 2026)
The handbook “Healthy Organization: What Is It and How Can It Be Achieved in the Croatian Context?” is intended for managers, employees, researchers, professionals, and students interested in developing organizations that promote employee well-being while ensuring sustainable organizational success. Based on the premise that managers and employees are equally important agents of organizational change, the handbook provides theoretical and practical guidelines for fostering healthy organizations adapted to the specific characteristics of the Croatian work environment. The first part of the handbook presents the concept of a healthy organization through an overview of relevant theoretical approaches and scientific findings, highlighting its key components and practical implementation guidelines. The second part presents the results of a pilot study conducted among Croatian employees, aimed at examining their perceptions of healthy organizations and their assessments of the organizations in which they work. The findings provide valuable insights into the characteristics of healthy organizations in the Croatian context, raise new research questions, and offer recommendations for improving work environments and employee well-being. The handbook serves as a useful resource for both personal and organizational development and contributes to the promotion of healthier organizations and a healthier society overall.